The nutritional knowledge of pregnant women - Książek, Piotr; Kozłowiec, Joanna; Kozłowiec, Monika (Polish Journal of Public Health, 2015)
Introduction. Rational nutrition of women during pregnancy has a great influence on the developing fetus. In the properly developing pregnancy, woman should eat 3-4 quality meals per day. What is more, for the proper development of the fetus, as well as the placenta, uterus and the mammary gland, it is necessary to consume high-value protein products. Moreover, vitamins and mineral compounds are important due to the serious implications that arise if not properly provided. Aim. The aim of the paper is to assess the nutritional practices, the level of knowledge held by pregnant women with respect to proper nourishment practices, and to define the influence of level of formal education achieved upon this issue. Material and methods. The research involved 87 pregnant women who were under the care of the outpatient women’s health centre and high-risk pregnancy unit of the Regional Specialist Hospital in Biała Podlaska. Results and discussion. According to most of the female respondents, information concerning proper nutrition of pregnant women is not generally available. Because of this, in completing the questionnaire, more than half of the subjects stated that they often consume white bakery products, white rice and refined pasta – with insufficient consumption of brown bread, rice and wholemeal pasta. Furthermore, while the respondents seem to consume the proper amount of potatoes, barely 8% consume other vegetables with the advised frequency. Moreover, only 31% of the respondents take-in fruits in necessary quantities. However, a majority of them frequently consume milk, yoghurt, cheese, kefir and buttermilk; plus, more than half of the respondents drink at least 1-2 litres of various kinds of liquids per day. Our results also reveal that they very rarely consume fresh fish, poultry and red beef meat, preferring cooked products. Indeed, the respondents stated that they consume meat and fish mainly in a fried form, while 52.9% of the women take-in fast food products. Of note, the surveyed women prefer animal fats. In addition, nearly 70% of the subjects consume too many eggs. Furthermore, more than 40% consume an excessive amount of sugar and sweets. To conclude, the proper amount of meals is consumed by only 52.7% of the respondents, no matter their formal education level. Conclusions. Many abnormalities were found while verifying negatively the hypothesis, according to which, level of formal education achieved has an impact on the increase of consciousness in terms of proper nourishment during the pregnancy.